2005
DOI: 10.1111/j.1366-9516.2005.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

How important is long‐distance seed dispersal for the regional survival of plant species?

Abstract: Long-distance seed dispersal is generally assumed to be important for the regional survival of plant species. In this study, we quantified the importance of long-distance seed dispersal for regional survival of plant species using wind dispersal as an example. We did this using a new approach, by first relating plant species' dispersal traits to seed dispersal kernels and then relating the kernels to regional survival of the species. We used a recently developed and tested mechanistic seed dispersal model to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 42 publications
2
99
0
Order By: Relevance
“…Within this suite of factors, gene flow promoted by long-distance dispersal agents, such as frugivores and pollinators (Bossart & Prowell, 1998;Soons & Ozinga, 2005;Trakhtenbrot et al, 2005) may be a powerful factor influencing observed patterns of genetic diversity. Despite the fact that many studies have focused on gene flow, questions still remain regarding the effects of pollination and seed dispersal agents on seedling survival and plant genetic diversity (Willson & Traveset, 2000;Levine & Murell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Within this suite of factors, gene flow promoted by long-distance dispersal agents, such as frugivores and pollinators (Bossart & Prowell, 1998;Soons & Ozinga, 2005;Trakhtenbrot et al, 2005) may be a powerful factor influencing observed patterns of genetic diversity. Despite the fact that many studies have focused on gene flow, questions still remain regarding the effects of pollination and seed dispersal agents on seedling survival and plant genetic diversity (Willson & Traveset, 2000;Levine & Murell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To compile our data set, we used six previous studies that summarized published dispersal information and addressed a large number of species (Willson 1993, Hughes et al 1994, Cain et al 1998, Bullock and Clarke 2000, Ness et al 2004, Vittoz and Engler 2007, as well as studies in which the dispersal distances were derived from models parameterized with field data (e.g., Sheldon and Burrows 1973, Augspurger 1986, Matlack 1987, Ernst et al 1992, Sto¨cklin and Ba¨umler 1996, Kiviniemi and Telenius 1998, Jongejans and Telenius 2001, Soons and Ozinga 2005. We additionally searched the ISI Web of Science for papers published up until 31 January 2012, using the keywords ''seed,'' ''dispersal,'' and ''distance.''…”
Section: Data On Seed Dispersal Distances and Plant Traitsmentioning
confidence: 99%
“…A recent global review of seed dispersal distances of over 300 species (Thomson et al 2011) revealed that plant height is more important than seed mass in determining seed dispersal distances. Similarly, for wind-dispersed species, seed release height is often a good predictor of dispersal distance (Soons and Ozinga 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malmqvist, 2002;Frisch & Threlkeld, 2005), wind (anemochory; e.g. Soons & Ozinga, 2005;Soons, 2006;Vanschoenwinkel et al, 2008a), animals (zoochory; e.g. Figuerola, Green & Santamaría, 2003;Frisch, Green & Figuerola, 2007;Van Leeuwen et al, 2012a) and more recent human activities can explain how aquatic species can persist in metacommunity structures (reviewed by Bilton et al, 2001) and how aquatic species spread around the world.…”
Section: Introductionmentioning
confidence: 99%